TEACHERS’ KNOWLEDGE OF THE DEBRIEFING PROCESS: THE NOMINAL GROUP TECHNIQUE APPROACH - Normariya Mohd Nor; Norhasmah Mohd Zain; Siti Nordarma Ab Rahman (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study explores teachers’ knowledge and application of debriefing practices, emphasizing the gaps between understanding and practical implementation. Using the Nominal Group Technique (NGT), seven experts participated in structured discussions to prioritize challenges and propose actionable solutions. Findings revealed significant barriers, including lack of standardized protocols, and insufficient institutional support, time constraints. This study underscores the importance of professional development, standardized frameworks, and institutional reforms to enhance the effectiveness of debriefing practices in education. Findings indicate that while 90.48% of educators understand debriefing goals, only 66.67% feel adequately trained, highlighting a critical need for professional development. Additionally, 95.24% believe debriefing improves student comprehension and critical thinking. This disconnect between understanding and practice underscores the importance of targeted training and institutional support. Further research is recommended to explore effective training modules, ultimately aiming to enhance the effectiveness of debriefing and improve educational outcomes. Finally, it is essential that debriefing is aligned with educational objectives to ensure its relevance and maximize its impact. When debriefing is linked directly to the curriculum and assessment goals, it provides teachers with concrete insights into how their reflective practices can improve both teaching methods and student learning outcomes. In conclusion, debriefing is a vital tool for enhancing teaching and learning in Malaysia. However, addressing gaps in training, resources, and institutional support is critical for its effective implementation. By aligning debriefing practices with cultural and curriculum contexts, we can empower educators to adopt reflective teaching methods and ultimately improve student outcomes.